(untitled) (Materiali di Estetica. Terza serie, 2023)
The article explores the idea of aesthetic autonomy and its relationship to the thought of Kant and Winckelmann. The text analyses how their thought influenced our understanding of beauty and eroticism, and how the notion of aesthetic autonomy helps us to better understand erotic art. Furthermore, the text examines the differences between sexual attraction and aesthetic pleasure, and how these two experiences can coexist or be separated. Overall, the text offers an in-depth reflection on aesthetic theory and its application to erotic art.